Memperkirakan saat Kematian (Postmortem Interval) Menggunakan Temuan Mikrobiom pada Setiap Tahap-Tahap Penguraian (Decomposition) - Putra, Afid Brilliana; Amin, Ihya Fakhrurizal; Fitriyasa, Rizky Dini; Najma, Najma; Safitry, Oktavinda (Fakultas Kedokteran Universitas Jenderal Soedirman, 2020)
Microorganisms play an important role in the process of corpse decomposition. The corpse's decomposition can indicate time since death or postmortem interval (PMI). Bacterial decomposition plays an important role in determining the time since death and has a significant impact on forensic investigations. Therefore, it is necessary to know the type of microbiome that appears at each stage of decomposition. Literature searching was conducted online and was carried out through 4 journal databases, including PubMed, EBSCOhost, ProQuest, and Cochrane. The literature is selected based on inclusion & exclusion criteria, then critically appraised using criteria from the University of Oxford's Center for Evidence-Based Medicine. Based on the results, obtained a systematic review, two prospective cohorts, and a cross-sectional study with good validity, importance and applicability. The study showed a relationship between time since death/PMI and colonization of certain bacteria, which may be related to alteration of oxygen levels. Facultative anaerobic bacteria appear in early stage of decomposition and shift into obligate anaerobic bacteria in the final stage of decomposition. The presence of certain types of microbiome can determine duration of decomposition and PMI objectively and quantitatively.